Study on Fabrication of Catalyst Based on Minerals of Tuyen Quang for Ozonization of Pulp Mill's Effluents - Bui, Tien Dung; Doan, Duy Hoang; Le, Quang Dien; Phan, Huy Hoang (Old Journal, 2017)
This study presented the fabrication of catalyst from iron ore of Tuyen Quang and application for ozonization of pulp mill's effluents. Iron ore was treated, refined and screened to obtain the particles with suitable size. The pretreated ore was subjected to fabricate the catalyst by oxidation at different conditions. Furthermore, the process for making of catalyst tablet was also studied to achieve the particles with big size for industrial catalyst. As-obtained catalyst was investigated in ozonization of An Hoa pulp mill's effluents to reduce the effluent colour. The results showed that catalyst from mineral of Tuyen Quang exhibited the high catalytic efficiency in reduction of colour of pulp mill's effluents. By ozonization with catalyst dosage of 5 mg/l, the colour degree of effluents was reduced by 60%. The pulp mill's effluents after treatment had the acceptable colour degree as Vietnam Standard on Environment.